Mechanical Thrombectomy in Pulmonary Embolism Associated with COVID-19: A "Clotography" Gallery. (November 2021) - Balanescu, Dinu V.; Kado, Herman S.; Mertens, Amy; Chand, Rajat; Savin, Michael; McNally, Vicki; Bowers, Terry R.
Venous thromboembolism from a "thrombotic storm"–like syndrome is a major cause of morbidity and mortality in patients with active or "recovered" COVID-19. Patients should be risk-stratified, optimally by a pulmonary embolism (PE) response team (PERT), and considered for escalation of care if found with intermediate or high-risk PE. We present a series of patients with COVID-19-associated PE and thrombotic storm with D-dimer >10 000 ng/mL who underwent successful mechanical thrombectomy for intermediate to high-risk PE. All patients had immediate improvement in hemodynamics and large amounts of thrombi were retrieved.